Sad Al-Dzara'i As a Preventive Norm in Family Law a Conceptual Analysis and Practical Application - Muhammad Zainuddin Sunarto; Ahmad Idhafi (FASYA Press, 2026)
This study examines sad al-dzara’i as a preventive normative principle in Islamic family law in response to contemporary socio-legal challenges. While existing scholarship predominantly emphasizes maqasid al-shari’ah as a framework for reform, limited attention has been devoted to the systematic operationalization of sad al-dzara’i as a structured preventive mechanism. This study addresses that gap by reconstructing its epistemological foundation and analysing its practical relevance in Indonesian family law contexts. Employing normative legal research with conceptual and statutory approaches, this article analyses classical ushul al-fiqh literature alongside Indonesian family law regulations. It further incorporates contextual socio-legal analysis of Aceh and Probolinggo, selected for their contrasting legal configurations: Aceh with formal Sharia-based regional regulations and Probolinggo within the national legal framework shaped by strong socio-religious authority. The findings indicate that sad al-dzara’i functions not merely as a theoretical doctrine but as an operational preventive paradigm reflected in regulatory safeguards, marriage age restrictions, and mediation mechanisms aimed at mitigating risks such as child marriage and family instability. The study concludes that integrating sad al-dzara’i within contemporary family law strengthens its anticipatory and adaptive character, aligning with maqasid al-shari’ah in safeguarding life, dignity, intellect, and lineage, while offering a preventive legal model for plural legal systems.